Feasibility of dosimetry with optically stimulated luminescence detectors in magnetic fields. (November 2017) - Spindeldreier, C.K.; Schrenk, O.; Ahmed, M.F.; Shrestha, N.; Karger, C.P.; Greilich, S.; Pfaffenberger, A.; Yukihara, E.G.
Abstract: The objective of this study was to analyze the applicability of optically stimulated luminescence detectors (OSLDs) for dosimetry in magnetic resonance (MR) guided radiation therapy devices with focus on dose dependence and angular dependence on the magnetic field strength. Precise detectors for dosimetry in high magnetic fields for such devices are still subject to research. In contrast to ionization chambers, OSLDs contain no air cavities, such that only minor changes in detector response with increasing magnetic field strengths are expected. To study the behavior of OSLDs in magnetic fields, Al2 O3 :C detector packages were irradiated at a 6 MV linac in a water phantom, while magnetic fields between 0.0 T and 1.0 T were applied. In order to study the angular dependence, the OSLD packages were rotated around the vertical axis for three different magnetic field strengths (0.0 T, 0.5 T, 1.0 T). Additionally, the angular dependence was measured at a clinical 0.3 T 60 Co device. The OSLDs were read out using a portable OSL reader and an automated Risø TL/OSL-DA-15 reader. Readout with the portable reader yielded package standard deviations of 1–2% and revealed no significant relation between dose response and magnetic field strength, while readout with the Risø reader resulted in standard deviations of only 1% and a significant decrease in response of −1.3% per T (95%-confidence interval: −1.9% to −0.7%). The angular dependence was not significantly influenced by the magnetic field. The small decrease in dose response supports the applicability of the OSL technique in MR-guided radiation therapy devices. We expect that no additional magnetic field correction factor has to be used when a calibration of the detectors in the magnetic field of such a device is performed. Highlights: Al2 O3 :C OSL detectors were tested for dosimetry in magnetic fields for MRgRT devices. A decrease in detector response of −1.3% per tesla (95%-CI: −1.9% to −0.7%) was found. The angular dependence of the OSLDs was not significantly influenced by the magnetic field.